Theoretical heterogeneous catalysis - Santen, R. A. van (World Scientific, 1991)
Includes bibliographical references and index.; The molecular basis of surface chemical reactivity forms the central theme of this book. It is an attempt to survey current understanding about the working of heterogeneous catalysts, emphasizing surface chemical bonding in relation to reaction mechanisms